Endovascular management of massive pulmonary embolism with clot fragmentation and suction - Belczak,Sergio Quilici (2013)
Massive pulmonary embolism with right ventricular dysfunction may be treated with thrombolysis, embolectomy, or percutaneous mechanical thrombectomy. This study describes our experience with two patients that had massive pulmonary embolism and were treated with percutaneous mechanical thrombectomy and reports on the mid-term results of this procedure. A 28-year-old man and a 70-year-old woman were diagnosed with deep venous thrombosis and massive pulmonary embolism. They first had lower limb edema followed by sudden onset of dyspnea. Their physical examination revealed edema, tachypnea, chest discomfort and jugular turgescence. Both needed to receive oxygen using a nasal cannula. Doppler ultrasound, echocardiography, and computed tomography angiography were used to establish the diagnoses. Patients underwent percutaneous mechanical thrombectomy using the Aspirex® system (Straub Medical), and their clinical condition and imaging study findings improved substantially. At mid-term follow-up, patient conditions were improving satisfactorily.